Effective and targeted latency reversal in CD4+ T cells from individuals on long term combined antiretroviral therapy initiated during chronic HIV-1 infection - Minh Ha Ngo; Joshua Pankrac; Ryan C. Y. Ho; Emmanuel Ndashimye; Rahul Pawa; Renata Ceccacci; Tsigereda Biru; Abayomi S. Olabode; Katja Klein; Yue Li; Colin Kovacs; Robert Assad; et al. (Emerging Microbes and Infections, 2024)
To date, an affordable, effective treatment for an HIV-1 cure remains only a concept with most “latency reversal” agents (LRAs) lacking specificity for the latent HIV-1 reservoir and failing in early clinical trials. We assessed HIV-1 latency reversal using a multivalent HIV-1-derived virus-like particle (HLP) to treat samples from 32 people living with HIV-1 (PLWH) in Uganda, US and Canada who initiated combined antiretroviral therapy (cART) during chronic infection. Even after 5–20 years on stable cART, HLP could target CD4+ T cells harbouring latent HIV-1 reservoir resulting in 100-fold more HIV-1 release into culture supernatant than by common recall antigens, and 1000-fold more than by chemotherapeutic LRAs. HLP induced release of a divergent and replication-competent HIV-1 population from PLWH on cART. These findings suggest HLP provides a targeted approach to reactivate the majority of latent HIV-1 proviruses among individuals infected with HIV-1.